Policy Implementation of Minister of Home Affairs Regulation No. 48 of 2021 concerning Development Planning and Supervision of Regional Government Implementation (Study at the Waropen Regency Inspectorate) - Surya, Muhammad; Masengi, Evi Elvira; Kairupan, Sisca (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this research is to see the performance of the Regional Inspectorate in carrying out the function of supervising government administration in Waropen Regency (Human Capital Based). Human resources are an instrument for increasing productivity to maintain organizational sustainability. One way of the Government's commitment to realizing good governance, especially eradicating corruption, collusion and nepotism, is to increase the role of the Government Internal Supervisory Apparatus (APIP). This research uses a qualitative method with a case study design. Data collection techniques are interviews, observation and studies and documents. The research results stated that the performance of the Waropen Regency Inspectorate was relatively low. In carrying out its supervisory function, the Waropen Regency Inspectorate does not use expert auditors. However, it is supported by auditors from the Financial Audit Agency (BPK). Developing organizational competence and working capabilities of the APIP team needs to be carried out in achieving clean governance. In achieving clean governance, it is necessary to pay attention to supporting and inhibiting factors as well as efforts to overcome obstacles in improving the performance of the APIP team